Analisis kecepatan pengiriman dan ketersediaan produk dalam layanan SAPA (Siap Antar Pesanan Anda) terhadap kepuasan konsumen di Alfamart Limusnunggal - Selviyanti, Dita; Wijayanti, Rini (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study aims to analyze the effect of delivery speed and product availability in the SAPA (Siap Antar Pesanan Anda– Ready to Deliver Your Order) service on customer satisfaction at Alfamart Limusnunggal. Delivery speed is measured through indicators such as timeliness, delivery process duration, and consistency between orders, while product availability is measured through the completeness of product types, stock continuity, and suitability of products with customer demands. Primary data were obtained through observation, interviews, and documentation at Alfamart Limusnunggal. Informants were selected using purposive sampling, with criteria being customers who had used the SAPA service. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that timely delivery speed and maintained product availability positively contribute to increasing customer satisfaction. Conversely, delayed deliveries and incomplete stock may reduce customer satisfaction. Overall, the SAPA service provides a practical solution for customers, but its success is strongly influenced by effective distribution management and stock control.